Diferentes niveles de proteína en dietas isoenergeticas de codornices en etapa de postura y su efecto sobre los parámetros productivos - Rojas Medina, Karla Jullay (2017)
The present work had as objective to evaluate different levels of protein in isoenergetic diets of laying quail and its effect on the productive parameters. It was realized in the Sector New Rinconada, District of Trujillo, Province of Trujillo, Department of the Freedom. The coordinates are: Latitude: 8º 5 '51.616' 'and Longitude: 79º 0' 8935 '', for which 500 quails distributed in a completely randomized design with five treatments, five replicates per treatment and 20 birds per repetition were used. Using treatments with protein levels: T1 with 16.5%, T2 with 18.5%, T3 with 20.5%, T4 with 22.5% and T5 with 24.5%. Duncan's analysis of variance and test found significant differences (P <0.05) for feed conversion, percentage of posture, weight and egg mass, not for feed intake, body weight and mortality (P> 0.05). That better productive parameters were obtained with levels 20.5, 22.5 and 24.5% of protein in the diet of quail.